Equine odontoclastic tooth resorption and hypercementosis. (4th July 2016) - Hole, S. L.; Staszyk, C.
Summary: Equine odontoclastic tooth resorption and hypercementosis (EOTRH) is a progressive and painful disease syndrome that affects aged horses. It affects incisor, canine and infrequently cheek teeth, and is characterised by gingival inflammation, oedema and recession, calculus deposition, feed accumulation, subgingival swellings with or without associated draining tracts, bulbous enlargement of teeth, tooth mobility, associated periodontal disease, tooth fracture and/or tooth loss. The aetiology of EOTRH is likely to be multi‐factorial. However, histopathological findings consistently suggest an aetiological contribution of initial biomechanical stresses and strains, followed by secondary involvement of micro‐organisms. Diagnosis is based on clinical presentation, age and radiographic changes including lytic changes, widening or loss of the periodontal ligament, hypercementosis, tooth fracture and alveolar bone loss. Treatment of EOTRH is not currently possible, but the condition can be managed to some degree, quite successfully for many years in some cases. However, the disease is progressive and invariably results in extraction of the tooth or teeth involved. The prognosis is most probably guarded at best and poor in most cases; however, complete removal of affected teeth carries a good prognosis for an improved quality of life in the short to medium term.